Returning biodiversity of rehabilitated forest on a coal mined site at Tanjung Enim, South Sumatra - HERY SUHARTOYO; ALI MUNAWAR; WIRYONO WIRYONO (Biodiversitas Journal of Biological Diversity, 2012)
Suhartoyo H, Munawar A, Wiryono. 2012. Returning biodiversity of rehabilitated forest on a coal mined site at Tanjung Enim, South Sumatra. Biodiversitas 13: 13-17. Restoring disturbed mined land is challenging since the outcomes of various rehabilitation procedures on mined sites in terms of vegetation structure, composition and ecological function are not presently understood, especially in the developing countries. This study examined the mechanism of biodiversity recruitment, especially on structural attributes of an undisturbed forest community and rehabilitated forests of different ages on sites disturbed by coal-mining operations at Tanjung Enim, South Sumatra. Un-mined forest was characterized by complex structural features including a dense stand of trees in a range of sizeclasses, an almost closed canopy, and a shrubby understorey. In contrast, young mined sites were characterized by a low density of woody stems, a relatively open canopy and herbaceous ground cover. Soil characteristics of rehabilitated site were progressing towards the reference site. The marked differences in structural complexity between unmined and mined sites suggest that it will take very long time for the mined sites to recover into their original conditions. So, more restoration intervention will be needed to speed the recoveryprocesses. Key words: restoration, mining, biodiversity, structural complexity.INTRODUCTIONRehabilitation of disturbed areas due to miningactivities is intended to assist the environment in returningto a stable and sustainable land use as soon as possible(Bell 1996; Parker 1997). The nature of the post-miningland use will depend on a number of factors including theecological potential of the mined environment and thewishes of the neighboring society. Currently, in Australia,many mining operations are using native plant species inrehabilitation programs leading to the establishment ofpastures and forests (Bell 1996, 2001; Gardner 2001),however in Indonesia, mining operators are mostly usingfast growing exotic species in their rehabilitation(Suhartoyo 2008), as in many other countries al around theworld (MartÃnez-Ruiz et al. 2007; Alday et al. 2010).As more mine operators need to establish their postmining plan